A novel positive feedback-loop between the HTLV-1 oncoprotein Tax and NF-κB activity in T-cells - Millen, Sebastian; Meretuk, Lina; Göttlicher, Tim; Schmitt, Sonja; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (Retrovirology, 2020)
BACKGROUND: Human T-cell leukemia virus type 1 (HTLV-1) infects primarily CD4+ T-lymphocytes and evoques severe diseases, predominantly Adult T-Cell Leukemia/ Lymphoma (ATL/L) and HTLV-1-associated Myelopathy/ Tropical Spastic Paraparesis (HAM/TSP). The viral transactivator of the pX region (Tax) is important for initiating malignant transformation, and deregulation of the major signaling pathway nuclear factor of kappa B (NF-κB) by Tax represents a hallmark of HTLV-1 driven cancer. RESULTS: Here we found that Tax mutants which are defective in NF-κB signaling showed diminished protein expression levels compared to Tax wildtype in T-cells, whereas Tax transcript levels were comparable. Strikingly, constant activation of NF-κB signaling by the constitutive active mutant of inhibitor of kappa B kinase (IKK2, IKK-β), IKK2-EE, rescued protein expression of the NF-κB defective Tax mutants M22 and K1-10R and even increased protein levels of Tax wildtype in various T-cell lines while Tax transcript levels were only slightly affected. Using several Tax expression constructs, an increase of Tax protein occurred independent of Tax transcripts and independent of the promoter used. Further, Tax and M22 protein expression were strongly enhanced by 12-O-Tetradecanoylphorbol-13-Acetate [TPA; Phorbol 12-myristate 13-acetate (PMA)]/ ionomycin, inducers of NF-κB and cytokine signaling, but not by tumor necrosis factor alpha (TNF-α). On the other hand, co-expression of Tax with a dominant negative inhibitor of κB, IκBα-DN, or specific inhibition of IKK2 by the compound ACHP, led to a vast decrease in Tax protein levels to some extent independent of Tax transcripts in transiently transfected and Tax-transformed T-cells. Cycloheximide chase experiments revealed that co-expression of IKK2-EE prolongs the half-life of M22, and constant repression of NF-κB signaling by IκBα-DN strongly reduces protein stability of Tax wildtype suggesting that NF-κB activity is required for Tax protein stability. Finally, protein expression of Tax and M22 could be recovered by NH4Cl and PYR-41, inhibitors of the lysosome and the ubiquitin-activating enzyme E1, respectively. CONCLUSIONS: Together, these findings suggest that Tax's capability to induce NF-κB is critical for protein expression and stabilization of Tax itself. Overall, identification of this novel positive feedback loop between Tax and NF-κB in T-cells improves our understanding of Tax-driven transformation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: HTLV-1; IKK2; M22; NF-κB; Protein stability; Tax-1